Modelling the landscape of professional nursing competence – A global perspective. (March 2020) - Weeks, Keith W.; Pontin, David
Highlights: Double the usual amount of submissions were submitted for the special digital edition. 25 papers were analysed for domain, practice area & nursing competence. Cognitive, functional, ethical, personal & meta competence elements were identified. Papers were mapped against an integrated model for competence in nursing education.